Association of microalbumiria, serum lipids and inflammatory markers in a rural black population in the Limpopo Province - Magwai, Thabo (My University, 2018)
Microalbuminuria (MA) is considered to be a strong and independent risk factor for cardiovascular disease (CVD), chronic kidney disease (CKD) and end-stage renal disease (ESRD). Cross sectional studies have indicated that microalbuminuria is also associated with cardiovascular risk factors such as dyslipidaemia and low grade inflammation. Hence, the aim of this study was to investigate the association of microalbuminuria with serum lipids [Total cholesterol (TC), Triglycerides (TG), High Density Lipoproteins Cholesterol (HDL-C), Low Density Lipoproteins Cholesterol (LDL-C), Lipoprotein a (Lp (a)] and inflammatory markers [C-reactive protein (CRP) and Interleukin-6 (IL-6)] in a rural black population. Methods: This is a cross-sectional study conducted in Dikgale Health and Demographic Surveillance System (HDSS) site and quantitative methods were used. The present study is part of a study titled “Prevention, control and integrated management of chronic diseases in a rural area, South Africa” conducted in the Department of Medical Sciences, University of Limpopo. In the above study blood samples were collected from 816 people aged 15 years and above. For the present study participants with HIV, macroalbuminuria, creatinine ≥170 μmol/land diabetes mellitus were excluded from the 816 people. Six hundred and two (602) participants fitted the inclusion criteria of the present study. Of the 602 participants 255 were men and 377 were women. From these participants, creatinine and albumin concentrations were measured in a morning spot urine sample and the albumin/creatinine ratio (ACR) was calculated. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured using OMRON M5-I. Serum lipids (TC, TG, HDL-C, and LDL-C) and glucose were determined using ILAB 300 plus. Lp (a) and hs-CRP were determined using IMMAGE 800 Immunochemistry System. Insulin and IL-6 were determined using ACCESS 2 Chemistry System. Data was analysed using SPSS version 22.0. Statistical tests used included Student T-test, ANCOVA, ANOVA, linear regression and logistic regression. Results: The levels of serum lipids and inflammatory markers in this study were similar in participants with and without microalbuminuria. In a linear regression model TG was the only lipid vi | P a g e parameter found to be associated with microalbuminuria (p = 0.018). Inflammatory markers were not associated with microalbuminuria. In a logistic regression model CRP and HDL-C showed negative association with microalbuminuria in men while in women no association was found. However men with a high CRP and a high TG were found to be more likely to have microalbuminuria (p = 0.007). Conclusion: A linear positive association was observed between microalbuminuria and TG in men and in women. The OR of having microalbuminuria was lower in participants with a high CRP, low HDL-C or in women with a high glucose. Women with a low HDL-C had higher OR of having MA and men with a high CRP and a high TG were found to be more likely to have microalbuminuria.
Thesis (M.Sc. (Medical Sciences)) -- University of Limpopo, 2018
Keywords: Cardiovascular disease; Chronic kidney disease; Albuminuria; Albuminuria; Bright's disease; Blood cholesterol.